Testing for multiple upper and lower outliers in an exponential sample. Issue 5 (24th March 2017) - Kumar, Nirpeksh; Lin, Chien-Tai
ABSTRACT: Due to wide applicability and simplicity, the exponential distribution is the most commonly used distribution in reliability engineering and other life testing experiments. In this paper a test statistic for testing upper and lower outliers simultaneously in an exponential sample is proposed. However, the distribution of test statistic under the alternative is rather intricate, the null distribution is derived and critical values are obtained. A simulation study is also carried out to compare the performance of test and is found that the test based on this statistic is more powerful than the other two selected tests.